Feasibility of a virtual service delivery model to support physical activity engagement during the COVID-19 pandemic for those with spinal cord injury. (30th September 2021) - Mehta, Swati; Ahrens, Jess; Abu-Jurji, Zeina; Marrocco, Stephanie L.; Upper, Randy; Loh, Eldon; Cornell, Stephanie; Wolfe, Dalton L.
Abstract : Background: The current pandemic has reduced access to safe, monitored physical activity (PA) programs for persons with spinal cord injury (SCI). The use of telerehabilitation has the potential for continuing activity engagement without risking virus exposure. The present study evaluates the feasibility and efficacy of an online group-based PA program for persons with SCI. Methods: This preliminary pre–post study delivered an online group-based PA program to persons with SCI. The program consisted of 1-hour sessions twice weekly for six weeks. Online PA satisfaction questionnaires were assessed at post-treatment. Psychosocial subscales from the NeuroQOL-SF were assessed. Results: Participants were adult females between 3 and 32 years post-injury, 1 tetraplegic and 3 paraplegics ( n  = 4). All participants were highly satisfied with the online instruction, overall content, and videoconferencing platform. Participants stated that the online program was beneficial for their overall physical and psychosocial wellbeing. The program resulted in improvement in anxiety and satisfaction with social roles and activities. Conclusion: The current pilot study demonstrates the acceptability and limited efficacy of an online PA program for those with SCI. The program resulted in improved overall perceived wellbeing and satisfaction with social roles and activities. These results have important implications for the clinical implementation of online PA programs in a hospital and community setting.